Migration, Social Policy and Social Work. Introduction to the Thematic Section - Vah Jevšnik, Mojca (Two Homelands, 2011)
The complex intertwinement of migration, social policy and social work can be approached and addressedin several manners. The author proposes a few directions for research within this relatively newmultidisciplinary fi eld that can be followed by scholars and policymakers and presents a few specifi cthemes that have proved to be of signifi cance in times of globalisation, increased (economic) competitivenessbetween states and world regions, and changing welfare regimes.